THE END OF SOCIAL WORK. - Kreuger, Larry W. (Journal of Social Work Education)
The article presents an evaluation of several factors affecting the demise of social work in the 21st century. The rise of hypertechnologies, such as electronic therapies, genetic-chemical revolution, and so on have been attributed to the end of social work. These technological developments will affect professional life as well. In the human services sector, a vast array of new technologies will supersede human service skills as clients negotiate solutions in totally electronic personal territories. The decline of the grand narratives has led to the trivialization of the social work knowledge base and the rise of pop-sociologistic writing in social work. Historically, social work has stood squarely on the side of the economically disadvantaged, recognizing that economic determinism creates system-victims. Radical dislocations in the social structure have also accounted for the decline of social work. Drastic changes in the world's political and economic structure, through the domination of worldwide corporations, will leave absolutely no viable role for professional social workers.